Role of celebrity endorsement in promoting employees’ organization identification: A brand-based perspective - Abdullah, Muhammad; Ghazanfar, Sidra; Ummar, Rakhshan; Shabbir, Rizwan (Frontiers in Psychology, 2022)
Celebrity endorsement has been used for decades to promote products to consumers. As employees are one of the primary stakeholders and are known as second consumers, their concerns about celebrity endorsement effectiveness and pride need attention for building their identification with an organization. This study investigated the internal branding process by examining employees’ brand orientation, celebrity-organization value congruence, and the accuracy of employee portrayal. Data is collected from a leading multinational bank in Pakistan through a structured questionnaire. Results of the study showed that when employees felt celebrity endorsement matched organizational values, the celebrity successfully portrayed actual corporate values. Thus, employees believed that endorsement effectively gained consumers' attention and built a strong corporate image. The study affirmed that employees' sense of pride toward their organization motivates them to identify with it. Furthermore, results showed that value congruence mediates the relationship between brand orientation and endorsement effectiveness, while pride mediates the relationship between endorsement effectiveness and organization identification. Service organizations could use brand orientation to gain accurate employee portrayal that revives their pride and attachment with the organization and enhances corporate identification. The future directions and limitations are discussed.